The European Court of Human Rights supervising the execution of its judgments. Issue 3 (September 2019) - Glas, Lize R.
The European Convention on Human Rights ('Convention') provides that the Committee of Ministers shall supervise the execution of the European Court of Human Rights' ('Court') judgments. This article aims to address the question whether, despite what the Convention provides, the Court is involved in supervising the execution of its judgments. Additionally, this article addresses the question what the Court does when it is engaged in this exercise. In order to answer these two questions, four aspects of the Court's practice that are linked to the execution process are examined. These are the four aspects of interest: just-satisfaction judgments under Article 41 ECHR, follow-up cases concerning individual measures, follow-up cases concerning general measures and the pilot-judgment procedure. The analysis of these aspects will lead to the conclusion that the Court indeed engages in supervising execution, but also that this does not mean that the Court is taking on the Committee's task and that supervising execution has not become in any way part of the Court's day-to-day work.